Freedom, Resentment and Anger: Emotions in Political Societies - Cíbik, Matej (Masarykova univerzita, 2022)
The paper seeks to explain how displays of emotion in the public sphere help to shape and structure our thinking about politics and how they challenge and transform the most fundamental philosophical concepts we use. The analysis focuses especially on the concept of freedom and the reactions accompanying its perceived lack or loss, including resentment, anger, fear and frustration. The aim is to show that no political theory is complete without analyzing emotions in the public sphere and assigning them their proper place. However, assigning emotions their proper place in political theory not only means recognizing their significance but also understanding the limits of their significance. The second part of the paper thus argues that assessing emotions relies at least in part on judgements concerning their 'appropriateness'. The paper then concludes with a version of Rawlsian reflective equilibrium, modelling the relation between displays of emotion in the public sphere and political theory.
Svoboda, odpor a hněv: Emoce v politických společnostech
Keywords: freedom; resentment; emotions; legitimacy; political realism; svoboda; politické emoce; rozhořčení; hněv; legitimita; realizmus